Validation of the Offending-Related Attitudes Questionnaire of CRIME-PICS II Scale (Chinese). (January 2017) - Chui, Wing Hong; Wu, Joseph; Kwok, Yan Yuen; Liu, Liu
This study examined the factor structure, reliability, and validity of the first part of the Chinese version of the CRIME-PICS II Scale, a self-administrated instrument assessing offending-related attitudes. Data were collected from three samples: male Hong Kong young offenders, female Mainland Chinese prisoners, and Hong Kong college students. Exploratory factor analysis and confirmatory factor analysis revealed a four-factor structure that differed from the one proposed by Frude, Honess, and Maguire. The Chinese version of the scale was found to have good internal consistency (α = .90) and good test–retest reliability ( r = .86) and also to present evidence of construct, concurrent, discriminant, and predictive validity. Overall, the Offending-Related Attitude Questionnaire (Chinese) proves to have great potential utility in the context of the Chinese criminal justice systems but will benefit from further validation studies.